Partial Characterization of the Factor Responsible For Tryptophanless Death in Bacillus subtilis - Barlati, Sergio (1970)
The decline in colony-forming ability observed during tryptophan starvation of Bacillus subtilis auxotrophs is a concentration-dependent phenomenon. It does not manifest itself when the initial cell concentration is 10(6) cells/ml or lower. This property has been used to test the killing activity of different fractions of the dying cells. Most of the activity recovered is found in the supernatant fluid of the starved culture. Sensitive and resistant strains can be identified. Active supernatant fluids can only be isolated from tryptophan auxotrophs sensitive to tryptophanless death. Resistant cells neither produce nor respond to the factor, and sensitive cells respond only when deprived of tryptophan. The killing activity is continuously produced and released into the medium at least up to 4 hr after removal of tryptophan from the culture. The killing activity is deoxyribonuclease-, ribonuclease-, and heat-resistant.